A case of multiple system atrophy. Issue 11 (November 2019) - Guo, Jing; Liu, Fuying; Liu, Tingting; Zhang, Xin; Luo, Yong
Multiple system atrophy (MSA) is the most rapidly progressive neurodegenerative disorder among the various types of synucleinopathies. The cause of MSA remains unknown, but it can involve the extrapyramidal system, the pyramidal system, the autonomic nerves and the cerebellum. The main clinical manifestations are Parkinson's symptoms, cerebellar ataxia, pyramidal tract signs and autonomic nervous system disorders. Depending on the initial predominant motor deficits, MSA is subclassified into either Parkinsonian type (MSA-P) or cerebellar type (MSA-C). MSA is rare in the Zunyi area of Guizhou Province, so when it is observed for the first time it often results in a convoluted diagnosis and treatment process, which takes a lot of time, money, manpower and material resources, which can also have a psychological impact on the patient. This report describes the case of a 60-year-old woman who presented with syncope for 1 year combined with dizziness for 1 day. She had been diagnosed twice with transient ischaemic attack in the previous 6 months. Cranial magnetic resonance imaging suggested widening of the cerebellar sulcus and mild cerebellar atrophy. Based on the patient's medical history, physical signs and auxiliary examinations, she was diagnosed with MSA-C.